PENGENDALIAN INTERNAL TERHADAP BIAYA OPERASIONAL PERUSAHAAN SEBAGAI BENTUK PERTANGGUNGJAWABAN KEPADA NEGARA PADA PT PERTAMINA HULU ENERGI WEST MADURA OFFSHORE - MESSILA, JIPSI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Operational costs is one of the most important part in preparing the income statement either small or large companies that have the type and volume of different activities. Operating costs is also essential to the sustainability of a company, it would require an accurate control of operational costs. Control of the company’s operating costs will help the carefull management to achieve corporate objectives. Form of setting goals and standards for the implementation of the control of each company is SOP (Standard Operating Procedure) serve as guidelines for any company, especially within large companies. With the SOP (Standard Operating Procedure) will assist the company in the exercise control over operations of the company. Internal control components according to the Warren Committee of Sponsoring Organization of Tradeway Commission (COSO), namely the control environment, risk assessment, control procedures, information and communication, and monitoring. Based on the five components of internal control, the authors conducted an analysis of internal controls over the company’s operating expenses as a form of accountability to the state in PT Pertamina Hulu Energi West Madura Offshore. Based on the above analysis has been done the author, it can be concluded that the internal control structure of the company’s operating costs are in accordance with the SOP (Standard Operating Procedure) is set.